A Confirmatory Factor Analysis of the Fraud Pentagon Instruments for Measurement of Fraud in the Context of Asset Misappropriation in Malaysia - Dani, Radziah Mohd; Mansor, Noorhayati; Awang, Zainudin; Afthanorhan, Asyraf (Journal of Social Economics Research, 2022)
The purpose of this study is to create and validate a tool for measuring constructs in the context of asset misappropriation among Malaysian public sector employees. The instrument was adapted from a prior study and adjusted to meet the needs of the present study. The target audience consists of public sector employees in the Malaysian Accountant General's Department. Cluster and proportional stratified random sampling techniques were used to choose a sample of 300 participants from the sampling frame of selected Accountant's General Department personnel throughout the country. Before the confirmatory factor analysis, the instrument was subjected to content validity and exploratory factor analysis (EFA). The confirmatory factor analysis (CFA) approach proved the presence of the perceived pressure, opportunity, rationalization, capability and arrogance constructs from the fraud pentagon theory. The CFA procedure eliminated five items because of inadequate factor loading (less than 0.6). All fitness indexes for fit categories reached the required level of model fitness. In addition, the average variance extracted (AVE) and composite reliability (CR), which represent convergent validity and construct reliability, respectively, have met the acceptable degree of model fit. The revised instrument for evaluating the perceived pressure, perceived opportunity, rationalization, capability, and arrogance constructs of the public sector in Malaysia is therefore valid and trustworthy for determining the issue of asset misappropriation among public sector employees in Malaysia.